Researches of Yield and Quality Characteristics of Lavandin (Lavandula X Ä°ntermedia Emeric Ex Loisel) Under Continental Type of Climate - YENÄ°KALAYCI, Ahmet; Gul, Kemal; Gunes, Mahmut (Journal of Science and Technology, 2019)
This study was carried out in Lavandin (Lavandula x intermedia Emeric ex Loisel) planted in the farmers' land in Kayseri, Turkey in 2015-2017. Kayseri is a region with a continental climate in Turkey's Central Anatolia Region. In this study, dry flower weight, essential oil content, essential oil yield, and essential oil components were investigated in demonstrations established in 14 locations in Kayseri. Accordingly, in Lavandin, with dry flower weight of 30-127 kg ha-1, the essential oil content was 2.72-9.00% and the essential oil yield was found between 17-77 lt ha-1. A total of 37 components were identified in the essential oil analysis including linalool (37.59-50.48%), linalyl acetate (1.10-40.23%), 1.8 cineole (2.09-17.72%), and camphor (4.13-9.21%). In Lavandin (Lavandula x intermedia Emeric ex Loisel) cultivation studies in the Kayseri, altitude below 1350-1400 m positive results were obtained in the region.